Análise da aglomeração a frio no processo HPS (Hybrid Pelletized Sínter) com ênfase nas matérias-primas envolvidas - Aercio Januzzi (2008)
ArcelorMittal Monlevade Steel works was motivated to study HPS (Hybrid Pelletized Sinter) process due to the similarity between the mix of iron ore from NKK Co and the natural fine iron ore from Andrade Mine owned by ArcelorMittal. The study began in the year 2000 and in the first quarter of 2002 the new plant facilities have started up with 100% of the Andrade sinter-feed (fine sinter-feed). Different characteristics in rawmaterials have introduced distortions in the original HPS technology in the Monlevade sinter plant. The fuel coating step of the original HPS could not be achieved in Monlevade plant. In this research, a study was carried out on the raw-materials effects in cold agglomeration phenomena and in the process conditions for establishing the conditions to recover the coke coating of the pristine HPS process. The burnt lime properties and its contribution to cold agglomeration were studied, reaching an increase in average size of the quasi-particles and in the sinter machine productivity.The other raw material such as limestone, serpentine, and manganese ore were studied and changes in size distribution (to increase the proportion of smaller fractions) were implemented aiming to improve the agglomeration performance. Laboratory and Industrial scale tests carried out in the Monlevade sinter plant yielded results showing that the changes made in the raw materials caused a positive and relevant outcome.